AB1209-HPR The prevalence of dental and sinus infection in patients with rheumatoid arthritis before biologic therapy initiation: usefulness of a systematic screening?. (15th June 2017) - Tawil, C; Descamps, E; Forien, M; Gardette, A; Palazzo, E; Ottaviani, S; Dieudé, P
Abstract : Background: Introduction of the biologic therapies has dramatically improved the outcome of severe rheumatoid arthritis (RA). Biologic therapies play a central role in the control of synovial inflammation. However they also decrease host defenses leading to an increased rate of infection. Because of their adverse effects, a careful assessment is needed before their initiation. A systematic assessment of dental or sinus infection before a biologic therapy is not required. Objectives: The aim of our study was to assess the prevalence and the usefulness of a systematic screening of oral (dental and/or sinus) infection of RA patients before biologic therapy initiation. Methods: This was a monocentric retrospective study. We included RA (ACR/EULAR 2010 criteria) patients with active disease despite disease-modifying anti-rheumatic drugs (DMARDs) and requiring biologic therapy initiation between 2010 and 2016. The following parameters were collected: demographic and disease characteristics, disease activity (C-reactive protein, disease activity score (DAS) 28), currents therapies (DMARDS, corticosteroids). Dental infection was assessed by stomatologist after clinical and panoramic dental X- ray evaluation. Sinusitis was defined on sinus computed tomography as partial or complete opacification of one or more sinus cavities. Factors associated with oral infections were analyzed in uni- and multivariate models. Results: We included 223 RA patients (79.4% of female, mean ± SD disease duration of 8.9±8.6 years). The mean age was 54±10.9 years, 70.8% rheumatoid factor (RF) positive, 84.4% anti–citrullinated protein antibody (ACPA) positive and 68.1% had radiographic damages. The mean DAS 28 was 5.5±2.6; 71% of patients received corticosteroids (mean 7mg per day of equivalent prednisone) and 63% methotrexate (mean 17.8mg per week). No patient had pain or other sinus or dental symptoms. Before biologic agent initiation, systematic dental and sinus screening revealed an oral infection in 31.5% of patients (dental: 20.2% and sinus: 14.8%). In univariate analysis, active smoking was associated with a higher risk of oral infection (OR=2.16 [1.02–4.57], p=0.038) and methotrexate with a lower rate (OR=0.43 [0.23–0.81], p=0.006). Corticosteroid, disease duration, DAS 28, RF, ACPA and structural damages were not associated with oral infection. No significant association was confirmed with oral infection using multivariate analysis. Conclusions: In our study, one third of RA patients requiring biologic agents had asymptomatic oral infection. The high prevalence of oral infection in RA patients suggests the usefulness of systematic dental and sinus screening before biologic therapy initiation. Disclosure of Interest: None declared